Customers’ perception of restaurant service quality : evidence from Malaysia / Voon Boo Ho ... [et al.] - Voon, Boo Ho; Kueh, Karen Meng Koon; Unggah, Lois; Chali, Raymond (Research Management Institute (RMI), 2009)
Restaurant plays a key role in attracting tourists and hence contributes significantly to a country’s economy. Restaurant service quality should therefore be well managed and sustained to ensure continuous and increased patronage. In this respect, the determinants and consequences of restaurant service quality need to be well understood. This paper presents the customers’ perception of restaurant service quality for a sample of 342 restaurant customers in Malaysia. The results showed that customers were generally satisfied with the service quality, price and variety of food. Reliability received the highest ratings followed by tangibles and responsiveness. Restaurants serving Western cuisine were rated better than the restaurants serving local food. Customer-perceived restaurant service quality was significantly correlated with the customer satisfaction and loyalty. Age and ethnic background did not affect perception of foodservice quality whereas gender influenced perceptions of food variety and overall satisfaction.